Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

QUESTION 4

4.1 Find the middle term in the expansion of [tex]$(3x - y)^4$[/tex] and simplify your answer.

4.2 Find the term that contains [tex]$x^5$[/tex] in the expansion of [tex]$(2x + 3y)^8$[/tex].


Sagot :

Certainly! Let's tackle each part of the question step-by-step:

### Part 4.1: Middle Term in the Expansion of [tex]\((3x - y)^4\)[/tex]

To find the middle term in the expansion of [tex]\((3x - y)^4\)[/tex], we can use the binomial theorem. The binomial theorem states:

[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k \][/tex]

For the expression [tex]\((3x - y)^4\)[/tex], we have [tex]\(a = 3x\)[/tex], [tex]\(b = -y\)[/tex], and [tex]\(n = 4\)[/tex].

Since [tex]\(n\)[/tex] is 4, there are 5 terms in the expansion (from [tex]\(k = 0\)[/tex] to [tex]\(k = 4\)[/tex]). The middle term is the one where [tex]\(k\)[/tex] is half of [tex]\(n\)[/tex], which is [tex]\(k = 2\)[/tex].

Use the binomial coefficient and substitute [tex]\(k = 2\)[/tex]:

[tex]\[ \binom{4}{2} (3x)^{4-2} (-y)^2 \][/tex]

Calculate the binomial coefficient:

[tex]\[ \binom{4}{2} = \frac{4!}{2!(4-2)!} = \frac{4 \times 3}{2 \times 1} = 6 \][/tex]

Now, substitute the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:

[tex]\[ 6 \cdot (3x)^2 \cdot (-y)^2 = 6 \cdot 9x^2 \cdot y^2 = 54x^2y^2 \][/tex]

Thus, the middle term in the expansion of [tex]\((3x - y)^4\)[/tex] is:

[tex]\[ 54x^2y^2 \][/tex]

### Part 4.2: Term with [tex]\(x^5\)[/tex] in the Expansion of [tex]\((2x + 3y)^8\)[/tex]

To find the term that contains [tex]\(x^5\)[/tex] in the expansion of [tex]\((2x + 3y)^8\)[/tex], we also use the binomial theorem. Here, [tex]\(a = 2x\)[/tex], [tex]\(b = 3y\)[/tex], and [tex]\(n = 8\)[/tex].

We need the term where the power of [tex]\(x\)[/tex] is 5. In each term of the expansion, the power of [tex]\(x\)[/tex] is given by [tex]\(n - k\)[/tex], so we set [tex]\(n - k = 5\)[/tex]. Therefore, [tex]\(k = 3\)[/tex].

Use the binomial theorem formula for the [tex]\(k\)[/tex]-th term:

[tex]\[ \binom{8}{3} (2x)^{8-3} (3y)^3 \][/tex]

Calculate the binomial coefficient:

[tex]\[ \binom{8}{3} = \frac{8!}{3!(8-3)!} = \frac{8 \times 7 \times 6}{3 \times 2 \times 1} = 56 \][/tex]

Now, substitute the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex], and the powers:

[tex]\[ 56 \cdot (2x)^5 \cdot (3y)^3 = 56 \cdot 32x^5 \cdot 27y^3 = 56 \cdot 864x^5y^3 = 48384x^5y^3 \][/tex]

Thus, the term that contains [tex]\(x^5\)[/tex] in the expansion of [tex]\((2x + 3y)^8\)[/tex] is:

[tex]\[ 48384x^5y^3 \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.